Effect of thermal shocks on the interfacial bond strength of sandwich composites built with rigid and soft materials produced through extrusion process - G. Sakthi Balan; S. Aravind Raj (Results in Engineering)
The mechanical behavior and adhesion strength of the sandwich composite, which consists of a flexible and a rigid material, were examined using extruded polylactic acid (PLA) and thermoplastic polyurethane (TPU). Three types of binders were combined with the appropriate hardeners to bond the extruded materials. The fabricated specimens are subjected to a different number of thermal shock cycles, with a maximum and minimum temperature of 80 °C and −18 °C, respectively. The sandwich composite's mechanical properties, including tensile, flexural, and impact strength, were assessed after 20, 40, and 80 cycles of thermal shock. The results indicated that the ductility of PLA material was significantly impacted by the thermal shock cycles. After completing the maximal thermal shock cycles, the composites joined with polyester resin exhibited a lower strength reduction in the impact specimens. Maximum tensile strength of 22.3 MPa, flexural strength of 31.6 MPa, and impact strength of 8.3 J were recorded prior to the application of thermal shocks to the specimens. The specimens that were bonded with epoxy resin recorded the maximal tensile, flexural, and impact strength. Following the thermal shock cycles, the composites bonded with epoxy resin exhibited a lesser reduction in tensile and flexural strength, while the composites bonded with polyester resin showed a lower strength reduction for impact specimens. The tensile and flexural specimens encountered a 7.54 % and 20.24 % reduction in strength, respectively, after undergoing 80 cycles of thermal shocks. The impact specimens experienced an 8.62 % reduction in strength.